6x-13=3(2x+9)

Simple and best practice solution for 6x-13=3(2x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-13=3(2x+9) equation:


Simplifying
6x + -13 = 3(2x + 9)

Reorder the terms:
-13 + 6x = 3(2x + 9)

Reorder the terms:
-13 + 6x = 3(9 + 2x)
-13 + 6x = (9 * 3 + 2x * 3)
-13 + 6x = (27 + 6x)

Add '-6x' to each side of the equation.
-13 + 6x + -6x = 27 + 6x + -6x

Combine like terms: 6x + -6x = 0
-13 + 0 = 27 + 6x + -6x
-13 = 27 + 6x + -6x

Combine like terms: 6x + -6x = 0
-13 = 27 + 0
-13 = 27

Solving
-13 = 27

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| y=-4/x+3 | | 8t-26=-30 | | 21/25=x/75 | | 7y=2+5x | | 2v+26=6v+30 | | 4(3y-2)+2(3y-2)= | | (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x | | 2x-2(6-4x)=6(x-5)-26 | | f-(41/3)=10 | | 12k+131=3(4k+43) | | 0=-16x^2+40x+2 | | 10(x+2)-2x=2(4x+2)-8 | | 1.2k+2.3=-0.5+7 | | (5u^2+2)-(7u^2-4u+6)= | | 2[3-(6-5r)]-r=-12+3(2+3r) | | (2w^2+3)+(5w^2-4W-6)= |

Equations solver categories